Court Constitution Delete Nomination Threshold President and Vice President - Guasman Tatawu; Wahyu Aliansa (JURNAL AKTA, 2026)
Thresholds in elections are often considered an obstacle for parties with small political bases to submit candidates for state leaders. Research this aim for the study base, focusing on the law used by the Constitutional Court in the provision of the nomination threshold, as well as its impact on the principles of democracy and representation politics in Indonesia, as outlined in Decision Number 62/PUU-XXII/2024. With a normative study, which focuses on the approach to legislation, concepts, and case studies, the research is conducted. This identifies the reasons behind the law's decisions. The results of the survey indicate that tests of the norms in Article 222 of the Election Law, related to the engineering constitution, may lead to weakening the principles of democracy and a decline in public trust in the government. Therefore, it is necessary to prioritize the interests of the people in the legislative and policy process. Additionally, the decision to introduce this potential change in national politics will enable smaller parties to nominate a State leader. However, there is nothing. This threshold also opens up the possibility for an oligarchy to establish a party for personal gain, which ultimately can weaken the mechanism of checks and balances within the state administration system.